Metodologia Hegelo-marxiana e centralidade do trabalho - Bavaresco, Agemir (2012)
BAVARESCO, Agemir; SCHÄFER, Márcio Egídio. Metodologia Hegelo-marxiana e centralidade do trabalho. Revista Dialectus, Fortaleza, ano 1, n. 1, p. 148-178, jul./dez. 2012.